“THE ECONOMIC MAGAZINE” FROM SIBIU, AN IMPERATIVE OF THAT TIME BETWEEN 1898-1918 - Rica Ivan (Agora International Journal of Economical Sciences)
“The Economic Magazine“, particularly meant on the service of the Romanian financial institutions, to which was given a common publicity organ ,of which they would use of, in all their practical needs and which to contribute for the spreading over of futuristic experiments of the ruling circles in the economic life of the Transylvanian Romanians, it put its service for the national economic interests by publishing wide lists of economic themes useful to all national economic fields .It had a much wider horizon than the one strictly connected to the financial-banking relations and interests. In this case, also, the Romanians national interests came first comparing to the strictly economic ones.